2017
DOI: 10.1007/s13178-017-0284-y
|View full text |Cite
|
Sign up to set email alerts
|

Sexism and Attitudes Toward Same-Sex Parenting in a Sample of Heterosexuals and Sexual Minorities: the Mediation Effect of Sexual Stigma

Abstract: The present study aimed to: (a) investigate the relationship between attitudes toward same-sex parenting and sexism both in heterosexuals and sexual minorities; (b) verify whether sexism predicted negative attitudes toward same-sex parenting via the mediating role of sexual stigma (sexual prejudice in heterosexual people and internalized sexual stigma [ISS] in lesbians and gay men [LG]). An Italian sample of 477 participants (65.6% heterosexual people and 34.4% LG people) was used to verify three hypotheses: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 81 publications
2
38
0
Order By: Relevance
“…As previous studies have shown (e.g. Pistella et al, 2018), gender inequalities and discriminatory treatments based on traditional beliefs about the superiority of men over women, sustain prejudices against sexual minorities. Public opinion can perceive LGBT groups' political demands for legal rights as a subversion of the social equilibrium based on the gender order, and in some cases political leaders ride the waves of the public fears.…”
Section: Discussionmentioning
confidence: 86%
“…As previous studies have shown (e.g. Pistella et al, 2018), gender inequalities and discriminatory treatments based on traditional beliefs about the superiority of men over women, sustain prejudices against sexual minorities. Public opinion can perceive LGBT groups' political demands for legal rights as a subversion of the social equilibrium based on the gender order, and in some cases political leaders ride the waves of the public fears.…”
Section: Discussionmentioning
confidence: 86%
“…The internal consistency reliability of the entire scale was α = 0.80 for the lesbian form and α = 0.81 for the gay man form. We used the total score of the scale, as done by other authors [ 51 ]. Higher scores indicate greater internalized heterosexism.…”
Section: Methodsmentioning
confidence: 99%
“…Future studies could also use a more representative sample of the whole sexual minorities by involving women too, in order to analyze even differences of bullying between lesbians and gay men. In fact, the sport environment is even hostile toward lesbian athletes (Symons, O'Sullivan, & Polman, 2016); future research on lesbian athletes should include different variables, such as sexism (Pistella, Tanzilli, Ioverno, Lingiardi, & Baiocco, 2018), heterosexism (Szymanski et al, 2008) or the pressures and risks associated with "hegemonic femininity" (Krane, 2001; Roth & Basow, 2004), and should be further investigated in relation to the different ways in which they experience explicit homophobia compared to gay athletes in sports-related contexts (Griffin, 1993).…”
Section: Limitations Of the Study And Future Researchmentioning
confidence: 99%